Role Played by the Passage of Time in Reversal Learning - Goarin, Estelle H. F.; Lingawi, Nura W.; Laurent, Vincent (Frontiers in Behavioral Neuroscience, 2018)
Reversal learning is thought to involve an extinction-like process that inhibits the expression of the initial learning. However, behavioral evidence for this inhibition remains difficult to interpret as various procedures have been employed to study reversal learning. Here, we used a discrimination task in rats to examine whether the inhibition produced by reversal learning is as sensitive to the passage of time as the inhibition produced by extinction. Experiment 1 showed that when tested immediately after reversal training, rats were able to use the reversed contingencies to solve the discrimination task in an outcome-specific manner. This ability to use outcome-specific information was lost when a delay was inserted between reversal training and test. However, interpretation of these data was made difficult by a potential floor effect. This concern was addressed in Experiment 2 in which it was confirmed that the passage of time impaired the ability of the rats to use the reversed contingencies in an outcome-specific manner to solve the task. Further, it revealed that the delay between initial learning and test was not responsible for this impairment. Additional work demonstrated that solving the discrimination task was unaffected by Pavlovian extinction but that the discriminative stimuli were able to block conditioning to a novel stimulus, suggesting that Pavlovian processes were likely to contribute to solving the discrimination. We therefore concluded that the expression of reversal and extinction learning do share the same sensitivity to the effect of time. However, this sensitivity was most obvious when we assessed outcome-specific information following reversal learning. This suggests that the processes involved in reversal learning are somehow distinct from those underlying extinction learning, as the latter has usually been found to leave outcome-specific information relatively intact. Thus, the present study reveals that a better understanding of the mechanisms supporting reversal training requires assessing the impact that this training exerts on the content of learning rather than performance per se.